Os assim chamados "corredores humanitários" e o possível papel da sociedade civil nas políticas de refúgio e migração regular - Morozzo della Rocca, Paolo (2018)
Once, the main problem for migrants and asylum-seekers was the refoulement at the borders. Today instead, for many more migrants the real borders are the consulates where it’s always more difficult to get a visa. In fact, only those who don’t have the right to remain in Europe are allowed to obtain a visa (as tourist). Otherwise, those who will be granted asylum don’t have right to apply for a visa, then they needs to fall in the smuggling organizations. The "humanitarian corridors" project offers legal ways to travel to Europe to those who have the right to protection. The project is realized and fully funded by private sponsors. To offer legal ways to asylum seekers and those who already have family ties in a European country is not the only answer, but it is certainly a good answer.